2018
DOI: 10.1159/000490621
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Bacterial Biofilm on Ureteral Stent and Studies on the Distribution of Pathogenic Bacteria and Drug Resistance

Abstract: Objective: This study aims to observe the morphological characteristics of bacterial biofilm on the surface of ureteral stents and analyze distribution characteristics of pathogens on the bacterial biofilm and drug resistance. Methods: Ureteral stents were sampled from 129 patients. A scanning electron microscope was used to observe the morphological characteristics of bacterial biofilms, and the Congo red medium was applied to screen bacterial biofilm strains on the renal pelvis section, ureter section, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
7
42
0
Order By: Relevance
“…However, just as other researchers, we find that the heparin coating did not decrease bacterial adhesion (30). Covering BraidStent ® with a heparin coating was intended to avoid the main source of the bacterial colonisation that occurs at the time of ureteral placement by the introduction of bacteria via the transurethral route into the urinary tract (31). The heparin coating was mainly released in the first 72 hours so as not to adversely affect the degradation rate, as our in vitro studies showed.…”
Section: Treatment Of Us Focuses On Preservation Of Renal Functionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, just as other researchers, we find that the heparin coating did not decrease bacterial adhesion (30). Covering BraidStent ® with a heparin coating was intended to avoid the main source of the bacterial colonisation that occurs at the time of ureteral placement by the introduction of bacteria via the transurethral route into the urinary tract (31). The heparin coating was mainly released in the first 72 hours so as not to adversely affect the degradation rate, as our in vitro studies showed.…”
Section: Treatment Of Us Focuses On Preservation Of Renal Functionsupporting
confidence: 58%
“…This might have weakened the anti-adhesive effect. The high bacteriuria rate observed in the study may be due to the fact that the tiny degradation fragments drained with the urine carry the unavoidable biofilm associated with any biomaterial placement in contact with urine (31). This biofilm remains isolated and protected on the stent surface in a current ureteral stent, but in a BUS, at a certain point the stent surface fragments over weeks, and sweeps biofilm bits containing planktonic bacteria along.…”
Section: Treatment Of Us Focuses On Preservation Of Renal Functionmentioning
confidence: 96%
“…Urinary tract infections (UTIs) are among the most common nosocomial infections and up to 90% of these are catheter associated. Indwelling catheters are a major risk factor for ascending UTIs and catheter-associated UTIs (CAUTIs) as well as other complications and are especially important in urology [1,2]. The most significant catheter complications are severe mechanical traumas such as perforation, partial urethral damage and uri-Urol Int 2021;105:278-284 DOI: 10.1159/000512370 nary leakage, symptomatic bacterial infection, anaphylaxis, catheter toxicity, and hypersensitivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…23 BraidStent Ò -H is designed so that heparin disappears in the urine in the first 48 to 96 hours; therefore, it does not affect stent degradation rates since heparin reduces the stent bacterial contamination that sometimes occurs due to bacteria entering at the time of ureteral placement by transurethral routes. 24 Nevertheless, the results were unsatisfactory since asymptomatic bacteriuria values of >30% rarely appear in contemporary clinical studies. 24,25 To understand these results, when evaluating any BUS, expelled stent fragments carry biofilm matrix on their surface.…”
Section: Discussionmentioning
confidence: 99%
“…24 Nevertheless, the results were unsatisfactory since asymptomatic bacteriuria values of >30% rarely appear in contemporary clinical studies. 24,25 To understand these results, when evaluating any BUS, expelled stent fragments carry biofilm matrix on their surface. Consequently, the breakdown of the biofilm matrix allows the release of planktonic bacteria in urine, which potentially provide a source of increased bacteriuria in the laboratory.…”
Section: Discussionmentioning
confidence: 99%